2017
DOI: 10.2147/ccid.s148499
|View full text |Cite
|
Sign up to set email alerts
|

The association between stress and acne among female medical students in Jeddah, Saudi Arabia

Abstract: IntroductionAlthough there is widespread acceptance of a relationship between stress and acne, not many studies have been performed to assess this relationship. The objective of this study was to determine the relationship between stress and acne severity.MethodsA cross-sectional study was conducted among 144 6th year female medical students 22 to 24 years in age attending the medical faculty at King Abdulaziz University. This study used the global acne grading system (GAGS) to assess acne severity in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
3
44
0
4
Order By: Relevance
“…CRH also stimulates steroidogenesis and sebaceous gland lipid production leading to acne. 13,30 72.22% of the patients had low self-esteem, mirroring the findings of Vilar et al 27 Appearance of patients having chronic recurring skin conditions like acne lies outside their control and can impact their interpersonal relationships resulting in a low-self-esteem. 19 Almost three in every four patients (72.22%) had high body image disturbance.…”
Section: Resultssupporting
confidence: 63%
“…CRH also stimulates steroidogenesis and sebaceous gland lipid production leading to acne. 13,30 72.22% of the patients had low self-esteem, mirroring the findings of Vilar et al 27 Appearance of patients having chronic recurring skin conditions like acne lies outside their control and can impact their interpersonal relationships resulting in a low-self-esteem. 19 Almost three in every four patients (72.22%) had high body image disturbance.…”
Section: Resultssupporting
confidence: 63%
“…Scores are reverse coded for four questions and summed for a total score ranging from 0-40, with high scores indicating higher perceived stress. The reliability of the PSS ranges from Cronbach α of 0.85 to 0.91 with a test-retest reliability of 0.85 [27][28][29].…”
Section: Evaluation Of Stress Factors (Esf) [25]mentioning
confidence: 99%
“…We read with great interest the paper by Zari and Alrahmani 1 investigating the relationship between stress and acne among female medical students. These findings are relevant as around 20% of young people are affected by moderate-to-severe acne, and indeed acne severity is associated with increased risks of anxiety, depression, and suicidal ideation.…”
mentioning
confidence: 99%
“… 2 The authors identified that “stress severity strongly correlated with an increase in acne severity,” and suggested that stress likely has an important role in the pathogenesis of acne. 1 However, the paper could have been taken further to better establish the true extent of this relationship, and ultimately whether certain patients will benefit from clinical interventions based on their perceived stress scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation